Acquiring skills : market failures, their symptoms and policy responses - Booth, Alison L.; Snower, Dennis J. (Cambridge University Press, 1996)
Technological change, unemployment and industrial restructuring have highlighted training and the acquisition of skills as a policy issue. There is widespread concern that employees are insufficiently skilled, and it is recognised that this deficiency can have serious economic consequences. The situation is likely to become particularly urgent, as the dramatic increase in the share of temporary and part-time employment in the OECD leads to a decline in the incentives to train. This 1996 book, from the Centre for Economic Policy Research, provides a systematic account of the causes, consequences, and policy implications of failure in training provision and skills acquisition in the industrial world. It explains why the market mechanism leads people to under-invest in skills and examines the empirical outcome of these problems using a portfolio of examples for European countries.